Strangers in the swarm - Kent, Michael (Chandos Publishing, 2012)
What happens economically, culturally and socially in file sharing ‘communities’? This chapter enters the Bit Torrent swarm and explores the complex, intricate and yet rule-bound relationships in this transitory community.